2016
DOI: 10.1146/annurev-genet-112414-054842
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology and Evolution of Cancer: The Ultra-Microevolutionary Process

Abstract: Although tumorigenesis has been accepted as an evolutionary process ( 20 , 102 ), many forces may operate differently in cancers than in organisms, as they evolve at vastly different time scales. Among such forces, natural selection, here defined as differential cellular proliferation among distinct somatic cell genotypes, is particularly interesting because its action might be thwarted in multicellular organisms ( 20 , 29 ). In this review, selection is analyzed in two stages of cancer evolution: Stage I is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 149 publications
1
98
0
1
Order By: Relevance
“…Although genetic instability is not a requirement for cancer development (10), cancers exhibit a mutator phenotype (11), which results in the often remarkable heterogeneity of cancers (12). Genetic instability allows cancer cells to develop resistance to all kind of therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic instability is not a requirement for cancer development (10), cancers exhibit a mutator phenotype (11), which results in the often remarkable heterogeneity of cancers (12). Genetic instability allows cancer cells to develop resistance to all kind of therapies.…”
Section: Introductionmentioning
confidence: 99%
“…We shall present the analysis of somatic mutations first. 1) Fitness-altering mutations in the soma leading to tumorigenesis -A mutation is assumed to affect fitness with probability r. Based on the analysis of 299 cancer driver genes (Bailey, et al 2018), we set r at 0.04 (See Methods; (Wu, et al 2016)). The number of genetic events needed to start tumorigenesis has been estimated to be 5 -10 (Fearon and Vogelstein 1990;Hanahan and Weinberg 2011).…”
Section: Fitness-altering Mutationsmentioning
confidence: 99%
“…Beyond driver and neutral (passenger) mutations, the existence of deleterious mutations in tumors has been controversial (Wu, et al 2016;Zapata, et al 2018). Such mutations presumably could slow down cancer evolution and should be relevant only when data on non-cancerous clonal expansions are included (see Chen, Ruan et al, unpublished results).…”
Section: Fitness-altering Mutationsmentioning
confidence: 99%
“…Given the complete genomic linkage of asexually reproducing populations (due to the lack of recombination) such as tumor cells, interference between positive and negative selection (known as the Hill-Robertson effect) [230] may be particularly strong when accompanied by high mutation rates [231]. Intriguingly, McFarland et al [232, 233] found that deleterious mutations significantly alter tumor progression by impeding the efficiency of positive selection.…”
Section: Evolutionary Forces Determining the Extent Of Genetic Hetmentioning
confidence: 99%